2018
DOI: 10.1038/s41598-018-30822-x
|View full text |Cite
|
Sign up to set email alerts
|

Stiff auxetics: Hierarchy as a route to stiff, strong lattice based auxetic meta-materials

Abstract: Using a combination of analytic and computational methods, we examine the effect of adding hierarchical substructure to an auxetic lattice. Our novel methodology, involving a coarse grain approach, allows for the analysis of hierarchically sub-structured lattices where direct computation would prove intractable. We show that through hierarchy one can create ultra-lightweight auxetic meta-materials of high strength and stiffness. Through scaling law arguments, we show that the benefits of hierarchical design ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 58 publications
(69 reference statements)
0
22
0
Order By: Relevance
“…Indeed, the limitations of the two length scales approach have been also recognized by other metamaterials communities. For example, a number of hierarchical mechanical metamaterials 25,26 with extraordinary and otherwise impossible combination of properties, such as high stiffness and auxetic behavior 27 have recently appeared in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the limitations of the two length scales approach have been also recognized by other metamaterials communities. For example, a number of hierarchical mechanical metamaterials 25,26 with extraordinary and otherwise impossible combination of properties, such as high stiffness and auxetic behavior 27 have recently appeared in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation was primarily focused on exploring the merits of introducing hierarchical triangular truss-like components within the rotating unit and analysing the effects of these structural frameworks on the mechanical properties of the studied systems. Previous studies on other hierarchical auxetic systems have shown that the introduction of hierarchy in such structures may be used to obtain enhanced mechanical properties and/or provide structural stability through smart design [23][24][25][26][27][28][29][30]. Hierarchical structures, which are defined as structures which are themselves made from structures [31], are not limited solely to fractal or fractal-like systems [25,32,33], but may also include the use of different geometries and mechanisms at separate hierarchical levels aimed at conferring additional enhanced properties to the system.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that materials with negative Poisson's ratio, negative thermal expansion, negative compressibility, and other anomalous characteristics attract considerable attention of researchers because they are interesting from the theoretical standpoint and have a potential in applications …”
Section: Introductionmentioning
confidence: 99%